Delta sigma digital analog converter circuit design for neurochemical sensing / Zurita Zulkifli ...[et al.] - Zulkifli, Zurita; Arshad, Noor Syazana; Mohamat Kassim, Nazirah; Sihab, Norsabrina; Yusuf, Rihana; Nordin, Shahila (UiTM Press, 2010)
The aim of this project is to measure dopamine signal current via In Vivo Voltammetry System. Voltammetry is a category of electroanalytical methods used in analytical chemistry. In voltammetry, information about an analyte is obtained by measuring the current as the potential is varied. In Vivo Voltammetry is used to measure dopamine signal current when potential applied to the dopamine while subject still alive. In Vivo Voltammetry system consists of several parts such as Op-Amp, Voltage Frequency Converter, Digital Analog Converter and Potentiostat. Specifically, this project is to design and simulate a Digital Analog Converter (DAC) by implementing Delta Sigma Modulator. Simulations are done in PSpice software. Delta Sigma DAC is chosen to meet the desired voltage output 900mV and frequency 4Hz. This type of DAC is different from other common used DAC because it provides high resolution for accuracy implementation. Potentiostat requires voltage supply from a high resolution, accurate and low speed DAC.